Global and Local Color Time Scales to Encode Timeline Events in Ion Trajectories for Glassies - Sharif, J. M.; Mohd Ali, Abdul Malik; Abdul Jamil, M. Mahadi (International Journal of Integrated Engineering, 2015)
Glassy compounds lead directly to high ionic conductivity. Ionic conductivity generates ion trajectories. However, these trajectories have been represented by two-dimensional graph in order to visualize the timeline events in ion trajectories. This study addresses this problem by encoding the timeline events in ion trajectories with global and local color scales. Two time scales have been introduced namely Global Color Time Scale and Local Color Time Scale. The rainbow color has been chosen to represent global time scale meanwhile solid color has been used to generate local time scale. Based on evaluation, these techniques are successful in representing timeline events in ion trajectories for understanding the complicated heterogeneous movement of ion trajectories.